Kontribusi Modal Sosial Dalam Pengembangan Desa Wisata Mas-Mas Kabupaten Lombok Tengah - Isnan Nursalim; Rosiady Husaenie Sayuti; Oryza Pneumatica Inderasari (Faculty of Social Science, Universitas Negeri Malang, 2021)
This study discusses the contribution of social capital in the development of the Mas-Mas Tourism Village. The method used is the Mixed method which is a combination of quantitative and qualitative approaches. The results of the study show the importance of social capital in the development of the Mas-Mas Tourism Village. Through the network created in the form of relationships between members of the organization and other stakeholders, resulting in community participation as measured by community involvement in training, mutual cooperation and promotion of the Mas-Mas Tourism Village. Values and norms are shown by local wisdom that is still maintained. This is because of the awiq-awiq or rules for tourists that must be obeyed and socialized to tourists. This is what increases public trust in tourism village managers, tourists and stakeholders. Factors that play a role in the development of the Mas-Mas Tourism Village are the driving factors and inhibiting factors. The right strategy is carried out by Mas-Mas Tourism Village in developing tourism for now is to optimize the potential of the community and innovate with the tourism programs offered.This study discusses the contribution of social capital in the development of the Mas-Mas Tourism Village. The method used is the Mixed method which is a combination of quantitative and qualitative approaches. The results of the study show the importance of social capital in the development of the Mas-Mas Tourism Village. Through the network created in the form of relationships between members of the organization and other stakeholders, resulting in community participation as measured by community involvement in training, mutual cooperation and promotion of the Mas-Mas Tourism Village. Values and norms are shown by local wisdom that is still maintained. This is because of the awiq-awiq or rules for tourists that must be obeyed and socialized to tourists. This is what increases public trust in tourism village managers, tourists and stakeholders. Factors that play a role in the development of the Mas-Mas Tourism Village are the driving factors and inhibiting factors. The right strategy is carried out by Mas-Mas Tourism Village in developing tourism for now is to optimize the potential of the community and innovate with the tourism programs offered. Penelitian ini membahas kontribusi modal sosial dalam pengembangan Desa Wisata Mas-Mas. Metode yang digunakan yaitu Mixed method yang merupakan gabungan antara pendekatan kuantitatif dengan kualitatif.. Hasil Penelitian menunjukan pentingnya modal sosial dalam pengembangan Desa Wisata Mas-Mas. Melalui jaringan yang tercipta berupa relasi antar anggota organisasi dan stakeholders lainnya menghasilkan partisipasi masyarakat yang diukur dari keterlibatan masyarakat dalam mengikuti pelatihan, gotong royong serta melakukan promosi Desa Wisata Mas-Mas. Nilai dan Norma ditunjukan dengan kearifan lokal yang masih terjaga. Hal ini karena adanya awiq-awiq atau aturan bagi wisatawan yang harus dipatuhi dan disosialisasikan kepada wisatawan. Hal ini yang membuat meningkatnya kepercayaan masyarakat kepada pengelola desa wisata, wisatawan dan stakeholders. Faktor yang berperan dalam pengembangan Desa Wisata Mas-Mas berupa faktor pendorong dan faktor penghambat. Strategi yang tepat dilakukan oleh Desa Wisata Mas-Mas dalam mengembangkan pariwisata untuk saat ini adalah mengoptimalkan potensi yang dimiliki masyarakat serta berinovasi dengan program wisata yang ditawarkan.